Efektivitas Media Audio Visual dalam Pembelajaran Sistem Pencernaan Manusia di Kelas VIII SMP - Parinduri, Wina Mariana; Rambe, Titin Rahmayanti; Lubis, Renni Ramadhani; Anggraini, Dini Puji; Kesumawati, Diah (Mahesa Research Center, 2025)
This study aims to determine the effectiveness of audio-visual learning media in improving student learning outcomes on the topic of the human digestive system in Grade VIII at SMP Al-Maksum. The method used was a quasi-experimental design with a quantitative approach. Data collection instruments included observation, learning outcome tests (pre-test and post-test), and documentation. The results showed an increase in student learning outcomes after the implementation of audio-visual media. During the pre-test, only 6 students (28.57%) achieved the minimum passing score (≥ 70), with an average score of 57. After being taught using audio-visual media, the number of students who met the minimum passing criteria increased to 18 (85.7%) with an average post-test score of 80. The N-Gain analysis showed a score of 55.14%, which falls into the “moderately effective” category. Therefore, audio-visual learning media are considered moderately effective in enhancing student learning outcomes on the digestive system topic and are recommended as an alternative instructional medium in science learning at the junior high school level.